SCREENING AND CONFIRMATION OF DIFFERENT SYNTHETIC ADULTERANTS IN SLIMMING PRODUCTS - Fakhri, Sajad; Mohammadi, Bahareh; Jalili, Ronak; Hajialyani, Marziyeh; Bahrami, Gholamreza (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The presence of synthetic drugs (as adulterant) in slimming herbal products of world markets has contravened the country’s law and has created many troubles for some consumers of slimming products. This study aims to use a simple and reliable method for simultaneously finding and validating the presence of possible adulterants in some slimming products, which could not be discriminated due to misleading packaging. Method: Fifteen slimming products were obtained from the Iran pharmaceutical markets. Liquid chromatography-ultraviolet and LC-mass spectrometry methods were performed for simultaneous screening and confirmation of adulterants. Results: The most abundant adulterant was Phenolphthalein, which has been used in 11 cases of the 15 slimming products. Furthermore, 5 products included caffeine, two included phendimetrazine, and two included protriptyline. Conclusion: The performed method was successful in detection of different adulterants. According to the presence of synthetic drugs in slimming herbal products, and their threats to people’s health it is necessary to create awareness in this case through public authorities.